Immunohistochemical Expression of CD27 in Bone Marrow Biopsies of Chronic Lymphocytic Leukemia Patients - Ahmed, Abeer A. (Iraqi Journal of Cancer and Medical Genetics, 2018)
Chronic lymphocytic leukemia (CLL) is the most frequent lymphoproliferative disorder in western world. Its main characteristic is proliferation of mature looking lymphocytes in bone marrow, blood and lymphoid tissues. Diverse clinical course, ranging from indolent course to aggressive disease could be seen .So, many efforts focus on finding reliable indicators that can help to predict the outcome or explain CLL clinical variability. Certain surface proteins such as CD38, CD49d and ZAP-70 are expressed on leukemic cell population and they are widely used as well-established prognosticators. Novel Markers such as CD27 has been emerged, but still there is controversy about its exact role in CLL prognosis. CD27 molecule is a member of the TNF receptor family, related to leukemic cells adherence to stromal cells, and to CLL prognostic factors. This study aimed to assess the immunohistochemichal expressions of CD27 in bone marrow biopsies of CLL patients and correlate it to the clinicopathological parameters. Methods: Cross sectional study was done on forty bone marrow paraffin blocks of untreated patients with CLL, collected from teaching laboratories of Medical City and National Center of Hematology, from November 2016 to June 2018. Immunohistochemical staining for CD27, CD38 antibodies were studied in relation to clinicopathological details. Results: Positive result of CD27 was found in (77.5%) of cases, with moderate intensity in (87.1%), score (1) in (61.3%) of cases. CD27 was significantly associated with Binet stage C, Rai stage IV , Hb level less than 10 g/dl and diffuse bone marrow involvement with ( P =0.021, 0.001, 0.018, and 0.001 respectively). No association could be established between CD27 and the well-established CD38 in our study group. The sensitivity of CD27 was (100%) for CLL high risk patients (Binet stage C). Specificity = 33.3% and accuracy of CD27 marker was 55%. Conclusions and recommendations: Immunohistochemistry can be used reliably to assess the expression of CD markers. Positive expression of CD27 in CLL cases significantly correlated with more advanced stage and CLL histological type of poor prognosis. We recommend further prospective studies to address if there is possible correlation between CD27 in CLL and chemosensitivity and other prognostic indicators.